THE EFFECT OF LIQUIDITY, SOLVENCY, ACTIVITY, AND PROFITABILITY ON FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES - Kensa, Kensa; Ekadjaja, Agustin (Graduate Program of Universitas Tarumanagara, 2025)
Indonesia is a country with various economic and business activities. With the development of economic activities, companies that have similar sectors in Indonesia have emerged, creating competition between these companies. The development of the company itself can be assessed from the corporation’s financial performance, if the corporation has financial performance. Financial performance describes ability of a corporation to produces profits effectively and efficiently over a set period by leveraging its assets. This analysis aimed to examine the effect of liquidity, solvency, activity, and profitability on the financial performance of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) over period of 2021 to 2023. For this research, purposive sampling was used, resulting in the selection of 120 companies from the non-cyclical consumer sector registered in IDX. Data processing applied in this research was Eviews 12 software. Hypothesis testing method employed was multiple linear regression. The model estimation applied was the Fixed Effects Model (FEM) to ensure alignment with multiple linear regression in analyzing the data. This research utilizes Return on Assets (ROA) to assess the financial performance of company The results obtained in this research indicate that liquidity have significant positive effect on financial performance. Solvency have significant negative effect on financial performance. Activity do not have a negative dan insignificant effect on financial performance. Profitability have significant positive effect on financial performance.